Stress Distribution and Displacement of Craniofacial Structures Following Rapid Maxillary Expansion in Different Types of Cleft Palate: A Three-Dimensional FEM Study - Esra Bölükbaşı; Berza Yılmaz; Sabri İlhan Ramoğlu (Turkish Journal of Orthodontics, 2021)

(untitled)
Objective: To evaluate displacements and stress distributions in finite element models (FEMs) of the craniofacial complex of 13-yearold male patient with complete unilateral cleft palate (UCP), a 15-year-old female patient with complete bilateral cleft palate (BCP), and a 15-year-old female patient with isolated cleft palate (ICP), which may respond differently to expansive forces.Methods: The FEMs were based on computed tomography scans of patients with UCP, BCP, and ICP who needed maxillary expansion. Von Mises stress distribution after 0.2 mm of expansion and displacements after 5 mm of expansion were investigated.Results: The highest amount of stress was observed in the ICP model. Surprisingly, no stress was noted around the nose in the BCP model. The amount of dentoalveolar expansion decreased from anterior to posterior on the cleft side of the UCP, BCP, and ICP models. In contrast, on the non-cleft side of the UCP model, the maximum dentoalveolar expansion occurred at the molar area, decreasing toward the anterior parts. Anatomical structures expressed posterior displacement in the UCP model. In the ICP model, structures close to midline showed anterior displacement, while structures in the lateral parts showed posterior displacement. In contrast with the other 2 models, the structures in the BCP model showed anterior displacement. Vertically, all the anatomic structures in the BCP model showed inferior displacement, while in the ICP and UCP models, only the structures close to the midline showed inferior displacement.Conclusion: Maxillary expansion caused different patterns of stress distribution and displacement in different types of clefts. Clinicians should consider the type of the cleft, and may expect differing patterns of widening following maxillary expansion.